On soft expert metric spaces - Ulucay, Vakkas; Sahin, Mehmet; Olgun, Necati; Kilicman, Adem (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this paper, we first introduce soft expert real number and soft expert point. Following this, the notion of soft expert metric over soft expert real sets has been defined and then soft expert metric spaces are investigated. Later, soft expert open ball, soft expert closed ball, soft expert neighborhood, soft expert open set and soft expert closed set are defined and studied some properties of these concepts.